Long-Term Oxygen Therapy in COPD: Factors Affecting and Ways of Improving Patient Compliance - Stamatis Katsenos; Stavros H. Constantopoulos (Pulmonary Medicine)
Long-term oxygen therapy (LTOT) is the cornerstone mode of treatment in patients with severe chronic obstructive pulmonary disease (COPD) associated with resting hypoxaemia. When appropriately prescribed and correctly used, LTOT has clearly been shown to improve survival in hypoxemic COPD patients. Adherence to LTOT ranges from 45% to 70% and utilization for more than 15 hours per day is widely accepted as efficacious. Although several studies have addressed the level of patients' adherence to LTOT, few have suggested or evaluated interventions that conduce to compliance enhancement. The lack of sufficient data regarding COPD patients following oxygen prescription is an enormous void that must be duly confronted to augment clinical effectiveness and cost containment for the long term use. The present review article highlights factors influencing the compliance of patients using LTOT and emphasizes novel strategies and interventions that may prove to be of significant benefit given the remarkably little current research appraising this issue. Therefore, additional research should be promptly performed to verify the efficacy of newly designed approaches in improving the outcomes of patients receiving LTOT.